The mobilisation of sub-national revenues is a decisive factor in the realisation of the 2030 Agenda - Christian von Haldenwang; Armin von Schiller (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
In 2015 the global community committed itself to an ambitious programme of reform. Achieving the Sustainable Development Goals and implementing the resolutions of the Paris climate conference require that great efforts are made – including those of a financial nature. Many states will have to ensure that untapped or barely used sources of income are developed. Sub-national units such as provinces, departments, districts, and cities will play an increasing role in the mobilisation of public revenues. They are also in the forefront with regard to realisation of the global reform agenda, as many of the objectives concern classic areas of activity of local government: schools, basic medical care, local road construction, public transport, construction of social housing, the supply of drinking water and disposal of waste water, refuse collection etc. These services are already the responsibility or co-responsibility of sub-national units. The mobilisation of revenues at sub-national level is therefore not only a financial necessity, it is also prudent from a development policy perspective: if the users and funders of a good match, there is a greater likelihood that the preferences of citizens will be observed and the use of funds monitored. In addition, local taxes and levies are often paid by a broad circle of citizens and companies. This serves to strengthen the relationship between governments and the governed. One thing should be clear in this: although many countries will exploit the scope for collecting local taxes and levies in the future, this potential is nevertheless limited. Many sub-national units will remain dependent on transfer payments from the central state. Cities, districts and the middle tier cannot solve the funding problem of the states on their own. However, they can help to place the provision of public services on a broader foundation of legitimacy and, in co-operation with the national level – for example via the exchange of information – improve fiscal policy as a whole. Consequently, they also contribute to overcoming problems of fragile statehood.
Keywords: 330; Governance